(untitled) (JURNAL KEPERAWATAN, 2018)
Abstract: Fatigue is one of the factors that can reduce the working capacity and the resistance of the body of workers. Organizational climate is the internal environment or psychological organization. Organizational climate will influence the practices and policies of human resources are accepted by its members. Through the initial survey, there are 33 nurses with a number of male 4 people and female 29 people. The purpose of the Study: the Purpose of this study to determine correlation of organizational climate and the work with job burnout of nurses in general Hospital GMIM Bethesda Tomohon. Research method: the method in this research is using the correlation test Pearson a sample of 33 nurses. The results of the Research: correlation of organizational climate with job burnout p value 0,921, r 0,018. Correlation of the work with work fatigue p value 0,162, r 0,249. Conclusion: there is no correlatetion of organizational climate with job burnout and not significant. There is no correlation the work with job burnout in Public Hospital GMIM Bethesda Tomohon. Keywords: organizational climate, work period, work fatigue Abstrak: Kelelahan adalah salah satu faktor yang dapat mengurangi kapasitas kerja dan ketahanan tubuh pekerja. Iklim organisasi adalah lingkungan internal atau psikologis organisasi. Iklim organisasi akan mempengaruhi praktik dan kebijakan sumber daya manusia yang diterima oleh anggotanya. Melalui survey awal terdapat 33 perawat dengan jumlah lakilaki 4 orang dan perempuan 29 orang. Tujuan Penelitian: Tujuan dalam penelitian ini untuk mengetahui hubungan iklim organisasi dan masa kerja dengan kelelahan kerja perawat di Rumah Sakit umum GMIM Bethesda Tomohon. Metode Penelitian: metode dalam penelitian ini adalah dengan menggunakan uji korelasi Pearson sampel sebanyak 33 perawat. Hasil Penelitian: hubungan iklim organisasi dengan kelelahan kerja p value 0,921, r 0,018. Hubungan masa kerja dengan kelelahan kerja p value 0,162, r 0,249. Kesimpulan: tidak ada hubungan iklim organisasi dengan kelelahan kerja dan tidak signifikan. Tidak ada hubungan masa kerja dengan kelelahan kerja di Rumah Sakit Umum GMIM Bethesda Tomohon. Kata Kunci: Iklim organisasi, masa kerja, kelelahan kerja